Macroeconomic effects of European integration on the Finnish economy: A simulation study - Ari Lahti (Bank of Finland, 1989)
The aim of this study is to discuss and to quantify the macroeconomic effects of further European integration on the countries outside the European Community. We use Finnish economy as an example in our quantitative analysis. However, for the most part of the study the analysis is in general level and thus can be applied to many other countries as well, especially to other EFTA countries. During the course of the study we assume that the integration process as described in the White Paper of 1985 is successful, and that Finland will not become a member of the Community. Instead, Finland will create close relations with the internal market by participating into the process of creating the European Economic Space (EES), together with other member countries of EFTA. By using the results of economic theory and existing studies on the effects of integration, we make a simulation study with an econometric macromodel to quantify the consequences of this alternative. This study is organized in the following way. Section 2 outlines the methodology used for this study. Section 3 contains a short description of the econometric macromodel used in the course of the study. In section 4 we discuss the design of the simulations for our purpose, and in section 5 we present the outcome of these simulations. Evaluation of the simulation results and concluding remarks are made in the final section. The simulation results presented in section 5 are the first quantitative estimates of macroeconomic consequences for the Finnish economy resulting from further European integration. According to the results, by participating into the integration process according to the way indicated by the government, there are clearly positive results from the integration to Finnish economy. The size of these effects indicate that the need for participating the economic integration process in Europe is obvious.
URN:NBN:fi:bof-201908051348
Keywords: 330